The bomber - Marklund, Lisa, 1962- (Pocket books, 2002)
Journalist Annika Bengtzon is asleep next to her husband when the call comes in at 3.22am on a frozen December night.It's the weekend;she's busy with two children and she still has Christmas shopping to do.But within minutes,all thoughts of seasonal goodwill are left behind.Annika is looking at a nightmare scene of police tape and rubble,trying to get the best possible picture for tomorrow's edition of her newspaper.A bomb has not only destroyed Stockholm's new Olympic arena just months before the Summer Games,it has blown someone to pieces.Putting a city on edge with fears of a terrorist on the loose,the Bomber will become Annika's biggest story - and maybe her last.Set against the breathtaking landscape of the Swedish winter,Liza Marklund's extraordinary writing,bone-chilling plot and irresistible heroine have created an international phenomenon as explosive as the Bomber's devastating blasts.